Verlust von hochaffinen Prostacyclin-Bindungsstellen bei Patienten mit Morbus Basedow - Virgolini, Irene; Weiss, K.; Hermann, M.; Sinzinger, H.; Höfer, R. (Nuklearmedizin - NuclearMedicine, 1989)
Prostacyclin (PGI2) mediates like TSH its cellular effects through the interaction with specific binding sites associated with the adenylate cyclase-cAMP-system. Binding of PGI2 and the generation of cAMP induced by PGI2 was evaluated in thyroid tissue obtained intraoperatively from euthyroid and hyperthyroid patients with diffuse normofollicular colloid struma. Transformation of the binding data according to Scatchard revealed heterogeneity of the PGI2 binding sites in the tissue of euthyroid patients: the high-affinity binding sites were calculated to be 0.68 ± 0.18 pmol/mg protein (Ka = 16.2 ± 9.1 nM) and the low-affinity binding sites to be 5.4 ± 1.6 pmol/mg protein (Ka = 151 ± nM). In contrast, in the hyperthyroid patients the low-affinity binding sites were not demonstrable and the high-affinity sites were significantly (p <0.001) reduced (0.17 ± 0.05 pmol/mg protein, Ka = 83.5 ± 19.6 nM). The competition of the agonist for the PGI2 sites in hyperthyroid patients was significantly (p <0.005) diminished (IC-50-values: 0.98 ± 3.1 vs 46.9 ± 12.1 μM). PGI2 stimulated cAMP-production in a dose-dependent manner. However, the basal value was significantly lower also in the hyperthyroid patients (p <0.001). The evidence of reduced PGI2 sites as well as reduced PGI2-induced cAMP production in the thyroid gland of patients with Graves’ disease may indicate an important role for PGI2 to play in the modulation of thyroid cell function.